EFEKTIVITAS PENGGUNAAN MODEL KOOPERATIF TIPE JIGSAW DAN STAD TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD IMBAS GUGUS DIPONEGORO KABUPATEN BLORA - Galih Gusti Prihatanti (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2017)
ABSTRACTThis study aims to try to overcome the problem of IPS learning by applying cooperative learning model of jigsaw and STAD type and to know the effectiveness of cooperative learning model of jigsaw and STAD type. The subjects of the study were V grade students from SDN Sumberjo 01, SDN Sumberjo 02, and SDN Pilang 01. The results showed that the average learning outcomes of the experimental class were 86.54, while the mean of the students' learning achievement was 69, 21. The result of t-test of the research was obtained by significance value of 2 tailed at 0.000, where 0.000 <0,05, meaning that there is effectivity of cooperative learning model type jigsaw and STAD to student learning result of IPS class V.Keywords: IPS Learning Outcomes, Jigsaw, STAD